Tempête sur la forêt française : reconstruire les paysages et améliorer la résilience des forêts dévastées - Yves Petit-Berghem (Bulletin de l’Association de Géographes Français)
Storms are among the most severe threats to forest and forestry nowadays. Research programs are now dedicated to a better understanding and analysis of damages in risks assessment schemes developed for and by foresters. As forests regularly experience storms, forest managers tend to anticipate those major risks by taking into account the vulnerability of trees and its associated parameters. When this event occurs, there is an urgent need to create a new landscape and to improve its resilience. This new landscape must also match with social expectations which need to take into account the characteristics and issues of very single territory. When facing a need of working together, is the landscape the accurate scale to reforestation projects. Is the landscape project process a way of better promoting civic dialogue, participatory process and common approach to the future of forests? The development of new territorialized and multi stakeholders approach generates a better value at the regional scale. This process allows the establishment of a type of forest which is less vulnerable to risks but also fits with social expectations. Above the usual proposals and guidelines, the major issue is the preservation of landscape identity as a major asset of its attractiveness.